ARRHYTHMIAS IN PREGNANT WOMEN - SIGNIFICANCE OF THE PROBLEM AND ITS SOLUTIONS - О. Е. Kolomatskaya; А. I. Chesnikova (SINAPS LLC, 2016)
The paper presents an analysis of a total of 5650 labor and delivery records of women in maternity departments of the city of Rostovon-Don for 2010-2014. Mean age was 28,26 years. We found out that cardiovascular diseases occurred in 25.58% of cases. There was a significant increase in the prevalence of cardiovascular diseases in pregnant women during 2010-2014. Arrhythmias were indicated typically of all the cases of cardiovascular diseases during pregnancy in 31,7%. Pregnant women with arrhythmias were assessed for concomitant diseases. We also outlined the main principles of patients' medical attention according to current National Guidelines.